Co-creating a large-scale adolescent health survey integrated with access to digital health interventions. (August 2020) - Peiris-John, Roshini; Dizon, Lovely; Sutcliffe, Kylie; Kang, Kristy; Fleming, Theresa
Aim: This paper describes how we engaged with adolescents and health providers to integrate access to digital health interventions as part of a large-scale secondary school health and wellbeing survey in New Zealand. Methods: We conducted nine participatory, iterative co-design sessions involving 29 adolescents, and two workshops with young people (n = 11), digital and health service providers (n = 11) and researchers (n = 9) to gain insights into end-user perspectives on the concept and how best to integrate digital interventions in to the survey. Results: Students' perceived integrating access to digital health interventions into a large-scale youth health survey as acceptable and highly beneficial. They did not want personalized/normative feedback, but thought that every student should be offered all the help options. Participants identified key principles: assurance of confidentiality, usability, participant choice and control, and language. They highlighted wording as important for ease and comfort, and emphasised the importance of user control. Participants expressed that it would be useful and acceptable for survey respondents to receive information about digital help options addressing a range of health and wellbeing topics. Conclusion: The methodology of adolescent-practitioner-researcher collaboration and partnership was central to this research and provided useful insights for the development and delivery of adolescent health surveys integrated with digital help options. The results from the ongoing study will provide useful data on the impact of digital health interventions integrated in large-scale surveys, as a novel methodology. Future research on engaging with adolescents once interventions are delivered will be useful to explore benefits over time.